An in vivo model for postinflammatory hyperpigmentation: an analysis of histological, spectroscopic, colorimetric and clinical traits. (13th December 2015) - Isedeh, P.; Kohli, I.; Al‐Jamal, M.; Agbai, O.N.; Chaffins, M.; Devpura, S.; Mahan, M.; Vanderover, G.; Lim, H.W.; Matsui, M.S.; Hamzavi, I.H.
Summary: Background: Acne vulgaris is a common condition that occurs in all skin types. Postinflammatory hyperpigmentation (PIH) is often associated with acne in patients of darker skin types, making it a common complaint in dermatology offices. Despite this, there is limited understanding of and effective treatment options for PIH. Objectives: The study objective was to validate an in vivo model for PIH and to compare the clinical, histological and spectroscopic characteristics of artificially induced PIH and acne‐induced PIH. Methods: A nonblinded, nonrandomized pilot study was performed. Thirty subjects served as their own control in which four sites treated with 35% trichloroacetic acid (TCA) solution and four truncal acne pustules were followed for 8 weeks and were evaluated clinically and histologically, and by colorimetry and spectroscopy. Results: The initial phases of inflammation between TCA‐ and acne‐induced PIH differ. However, clinical evaluations were similar on and after day 14. Acne‐ and TCA‐induced lesions were clinically, histologically and spectroscopically indistinguishable at day 28. Conclusions: Clinical, spectroscopic and histological similarities of acne‐induced and TCA‐induced PIH at day 28 suggest that TCA‐induced PIH can be a reproducible model for the study of acne‐induced PIH. Abstract : What's already known about this topic? Postinflammatory hyperpigmentation (PIH) is skin discoloration due to multiple insults and more frequently affects darker‐skinned patients. However, we don't know if different causes of PIH have similar clinical and spectroscopic properties. What does this study add? A model to induce PIH has been introduced. It possesses similar clinical, spectroscopic and histological properties as acne‐induced PIH. This model will allow us to design future structured mechanistic studies to help manage PIH. Linked Comment: Youn, Br J Dermatol 2016; 174: 721–722 .